Heterozygous missense variant in GLI2 impairs human endocrine pancreas development - Laura M. Mueller; Abigail Isaacson; Heather Wilson; Anna Salowka; Isabel Tay; Maolian Gong; Nancy Samir Elbarbary; Klemens Raile; Francesca M. Spagnoli (Nature Communications, 2024)
Abstract Missense variants are the most common type of coding genetic variants. Their functional assessment is fundamental for defining any implication in human diseases and may also uncover genes that are essential for human organ development. Here, we apply CRISPR-Cas9 gene editing on human iPSCs to study a heterozygous missense variant in GLI2 identified in two siblings with early-onset and insulin-dependent diabetes of unknown cause. GLI2 is a primary mediator of the Hedgehog pathway, which regulates pancreatic β-cell development in mice. However, neither mutations in GLI2 nor Hedgehog dysregulation have been reported as cause or predisposition to diabetes. We establish and study a set of isogenic iPSC lines harbouring the missense variant for their ability to differentiate into pancreatic β-like cells. Interestingly, iPSCs carrying the missense variant show altered GLI2 transcriptional activity and impaired differentiation of pancreatic progenitors into endocrine cells. RNASeq and network analyses unveil a crosstalk between Hedgehog and WNT pathways, with the dysregulation of non-canonical WNT signaling in pancreatic progenitors carrying the GLI2 missense variant. Collectively, our findings underscore an essential role for GLI2 in human endocrine development and identify a gene variant that may lead to diabetes.